The Philippeion at Olympia: The True Image of Philip? - Denkers, MrieAnn Katherine (My University, 2012)
The aim of this thesis has been to consider how Philip II of Macedonia presented himself to the Greek peoples after the Battle of Chaeronea in 336 BC. It examines the context and program of the Philippeion at Olympia in order to determine how Philip II negotiated his royal status in response to Greek opinion. This study takes into account the traditional role of the Macedonian kings, how they typically portrayed themselves, and to what purpose. It also explores Philip's propaganda specifically and the differing responses of various Greek peoples.
Although Philip's role as Hegemon of the League of Corinth seems to be at odds with the Philippeion's classification as a victory monument and a display of the king's authority, further examination reveals that the Philippeion conforms with Philip's program of propaganda. It's message is also adaptable to the various perceptions of the Greek peoples as well as any Macedonian viewers.
Keywords: Philip II of Macedonia; Philippeion; Philippeum; Olympia; Chaeronea; Macedonian kingship; Classical Archaeology and Art History; Other Classics; Classical Archaeology and Art History